Isolation and molecular characterization of Xylella fastidiosa from coffee plants in Costa Rica - Aguilar Álvarez, Estela Yamileth (2008)
Copyright The Microbiological Society of Korea and Springer-Verlag Berlin Heidelber GmbH 2008. / . Datos incluidos por Lisela Moreira Carmona.